Design of alternative binders for hard materials. (February 2020) - de Nicolás, M.; Besharatloo, H.; Alvaredo, P.; Roa, J.J.; Llanes, L.; Gordo, E.
Abstract: In the last years, a special interest has emerged towards the total or partial substitution of traditional cemented carbides composing elements. In this study, a systematic methodology is presented and used to design iron-based binders for WC and Ti(C, N) ceramic phases. First, metal alloy phase diagrams were simulated by means of Thermo-Calc® software, combining several alloying elements (Ni, Al, Cr, Mo and C) to fulfil the following criteria: provide high corrosion resistance, least number of phases present at room temperature and solidus-liquidus temperatures below 1500 °C. Two final compositions were chosen: Fe15Ni10Cr and Fe15Cr10Al. Next step was to validate the critical temperatures by means of differential thermal analysis tests and, finally, high-temperature wetting experiments were conducted to measure the contact angle between molten metal and ceramic phases. Resultant metal-ceramic region was studied by means of field emission scanning electron microscopy, energy dispersive X-ray spectroscopy and nanoindentation techniques. As a proof of concept, samples with 80 vol% of Ti(C, N) and WC ceramic phases were prepared for a basic characterization. Both ceramic reinforcements were compared, and the presented methodology could satisfactorily be validated as a design procedure of alternative binders for hard materials. Highlights: A flexible and systematic methodology is proposed for the design of alternative hard materials. Fe alloys are used as alternative binders, combining them with WC and Ti(C, N). Thermodynamic simulation is used as a tool for the design of binder and hard material compositions. Simulation is validated and hard materials are processed, proving method effectiveness.